The Development of Exegesis in Indonesia - Idil Hamzah (The International Journal of Pegon : Islam Nusantara civilization, 2023)
This paper examines the Adaby Ijtima'i style in Daud Ismail's interpretation of al-Munir. This style of interpretation explains the instructions for the verses of the Qur'an related to the conditions of society and efforts to overcome the problems of society by presenting the instructions for the verses in language that is simple to comprehend and implement in their daily lives. The most important aspect of the Adaby Ijtima'i style of interpretation is that the Qur'anic texts are connected to the realities of people's lives, social traditions, and civilizational systems so that they can be applied to problem-solving. Using a descriptive-analytic method to manage data, qualitative research, which is library research, was employed for this study. In his commentary, Daud Ismail allegedly applied the Adaby Ijtima'i interpretation style to the verses of the Qur'an. These signals can be found, among other places, in the writing of his commentary using the Bugis script lontara with the intention of facilitating public comprehension of the Qur'an, as well as in various interpretations, one of which is found in the QS. Al-Maidah Daud Ismail responds to the bad practices of Bugis society, such as abbotoreng (gambling) and drinking tuak pai'e (bitter wine), and then discusses the prohibition of Abberhalae (idol worship), such as batue (stones), pong ajue, etc (trees). and bring offerings such as sokko, inanre madupang-dupang Iyarega na itello (glutinous rice, assorted rice, and eggs) Tulisan ini mengkaji corak Adaby Ijtima'i dalam tafsir Daud Ismail terhadap al-Munir. Corak tafsir ini menjelaskan petunjuk ayat-ayat Al-Qur'an terkait dengan kondisi masyarakat dan upaya mengatasi permasalahan masyarakat dengan menyajikan petunjuk ayat-ayat tersebut dalam bahasa yang mudah dipahami dan dilaksanakan dalam kehidupan sehari-hari. Aspek terpenting dari corak penafsiran Adaby Ijtima'i adalah bahwa teks-teks Al-Qur'an terhubung dengan realitas kehidupan masyarakat, tradisi sosial, dan sistem peradaban sehingga dapat diterapkan pada pemecahan masalah. Dengan menggunakan metode deskriptif-analitik untuk mengelola data, penelitian kualitatif yang merupakan penelitian kepustakaan digunakan untuk penelitian ini. Dalam tafsirnya, Daud Ismail diduga menerapkan corak tafsir Adaby Ijtima'i pada ayat-ayat Al-Qur'an. Sinyal-sinyal tersebut antara lain dapat ditemukan dalam penulisan tafsirnya menggunakan aksara Bugis lontara dengan maksud memudahkan pemahaman masyarakat terhadap Al-Qur'an, serta dalam berbagai penafsiran, salah satunya ditemukan dalam QS. Al-Maidah Daud Ismail menanggapi praktik buruk masyarakat Bugis, seperti ab botoreng (judi) dan minum tuak pai'e (anggur pahit), dan kemudian membahas larangan Abberhalae (penyembahan berhala), seperti batue (batu), pong ajue, dll (pohon). dan membawa sesaji seperti sokko, inanre madupang-dupang Iyarega na itello (beras ketan, aneka beras, dan telur)